2022
DOI: 10.1101/2022.04.28.489942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immediate myeloid depot for SARS-CoV-2 in the human lung

Abstract: In the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, considerable focus has been placed on a model of viral entry into host epithelial populations, with a separate focus upon the responding immune system dysfunction that exacerbates or causes disease. We developed a precision-cut lung slice model to investigate very early host-viral pathogenesis and found that SARS-CoV-2 had a rapid and specific tropism for myeloid populations in the human lung. Infection of alveolar macrophages was pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…An important finding of our study is that adipocytes are not the only target of SARS-CoV-2 in adipose tissue, as we also detect SARS-CoV-2 RNA in a subset of inflammatory adipose tissue-resident macrophages. This finding is consistent with recent reports that SARS-CoV-2 can infect macrophages from the lung and secondary lymphoid organs, driving inflammatory pathology ( 38 , 99 104 ). In our study, we did not detect infectious virus release, suggesting abortive infection of adipose tissue macrophages.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An important finding of our study is that adipocytes are not the only target of SARS-CoV-2 in adipose tissue, as we also detect SARS-CoV-2 RNA in a subset of inflammatory adipose tissue-resident macrophages. This finding is consistent with recent reports that SARS-CoV-2 can infect macrophages from the lung and secondary lymphoid organs, driving inflammatory pathology ( 38 , 99 104 ). In our study, we did not detect infectious virus release, suggesting abortive infection of adipose tissue macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…In other tissues, whether macrophages can be productively infected remains debated. Two studies show productive infection of human alveolar macrophages and MDMs ( 103 , 104 ). However, numerous other studies report abortive infection of monocytes, macrophages, and MDM, hypothesizing that low ACE2 expression or pyroptosis prior to virus production and release lead to abortive infection ( 38 , 39 , 105 107 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with published scRNA sequencing analyses on ACE2 mRNA expression across cell types ( 20, 2729 ). A recent preprint reported ACE2-positive macrophages in lung explants infected ex vivo , as determined by immunofluorescence ( 30 ). These data suggest that both ACE2-positive and ACE2-negative macrophages are present in SARS-CoV-2-infected lungs.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with published scRNA-seq analyses on ACE2 mRNA expression across cell types (20,(27)(28)(29). A preprint study reported the presence of ACE2-positive macrophages in lung explants infected ex vivo, as determined by immunofluorescence (30). These data suggest that both ACE2positive and ACE2-negative macrophages are present in SARS-CoV-2-infected lungs.…”
Section: In Vitro Models Of Ace2-positive and Ace2-negative Macrophagesmentioning
confidence: 87%